Characterization of maize leaves and of sugarcane bagasse to elaborate of a mixed cellulose pulp - Prado-Martínez, Maribel; Anzaldo-Hernández, José; Becerra-Aguilar, Bruno; Palacios-Juárez, Hilda; Vargas-Radillo, José Jesús; Rentería-Urquiza, Maite (Instituto de Ecología, A.C., 2012)
This article presents the results obtained in chemical and morphological, characterization of corncob leaves (Zea mays), and bagasse of sugarcane (Saccharum officinarum). Percentage of α-cellulose,holocellulose, lignin and ashes, according to the Tappi standards and the Jayme-Wise methodfor each component, were analyzad. Biometric properties of each plant fibers (length and diameter,wall thickness and lumen diameter) were determined. Indices of quality of paper pulp for paper werealso estimated. This study was conducted in order to get information of both plants for further treatmentof pulping, bleaching and mixing, to obtain an optimal cellulosic pulp, from their waste. Theresults indicate that the content of holocellulose in the leaves of maize ear is in the range of materialscommonly used in the production of pulp for paper and is close to that observed in sugarcane bagasse.